Mechanism of hedysari radix praeparata cum melle and curcumae rhizoma herb pair in colitis-associated colorectal cancer through the MAPK/NF-κB signaling pathway: an investigation in vivo and in vitro - Liu, Ting; Zhang, Yugui; Gao, Feiyun; Zhang, Zhuanhong; Wang, Maomao; Ma, Cui; Wang, Yanjun; Ma, Dingcai; Wang, Zhe; Yan, Xingke; Li, Yuefeng (Frontiers in Chemistry, 2025)
IntroductionAstragali Radix (AR) - Curcumae Rhizoma (vinegar processed, CR) herb pair was recorded in ‘YIXUE ZHONGZHONG CANXILU’ to treat colitis-associated colorectal cancer (CAC). Hedysari Radix (HR) was categorized under the AR entry in ‘SHENNONG BENCAO JING’. HR is still an alternative to AR paired with CR clinically in northwest China. Hedysari Radix Praeparata Cum Melle (HRPCM) is a product that HR fries with honey to enhance the therapeutic effect. However, the mechanism of HRPCM paired with CR (HRCR) in CAC needs to be further elucidated.MethodsHRCR-MIAS were prepared using the eversion intestinal sac method. UHPLC Q-Exactive-MS investigated the compositions in HRCR-MIAS. Then, the mechanism of HRCR in CAC mice was predicted based on network pharmacology analysis in combination with the compositions in HRCR-MIAS. The pharmacodynamic effects of HRCR-MIAS for SW620 colon cancer cells were invested in vitro. The efficacies of HRCR low-, middle-, and high-dose groups (HRCR-L, 3.413 g/kg; HRCR-M, 6.825 g/kg; HRCR-H, 13.650 g/kg) in CAC mice were explored. Enzyme-linked immunosorbent assay (ELISA) kits were employed to assay The inflammatory factors levels, like IL-1β, IL-6, IL-10, and TNF-α in serum. The expressions of the intestinal permeability proteins, such as Claudin-1, Occludin, and ZO-1, were detected via immunohistochemical (IHC) analysis. Finally, the predicted signalling was verified by Western blot (WB).Results855 common components were identified in HRCR and HRCR-MIAS, and 25 specific components in HRCR-MIAS were pointed out. Based on network pharmacology analysis, the inflammatory response and the cross-linked MAPK signalling and NF-kB signalling were predicted to be the main reasons for HRCR in CAC. HRCR-MIAS inhibited the proliferation, induced apoptosis, regulated the cell cycle progression, and restrained the SW620 cells’ ability to migrate and invade in vitro. The outcomes of the WB experiment exhibited that HRCR-MIAS inhibited the expression of key proteins such as MEKK1, RAS, ERK, IKB and NF-kB in the MAPK/NF-kB signalling pathway of SW620 cells. The study in vivo found that the different doses of HRCR recovered the loss of body weight, the shortened colon length, the increased tumour counts, the abnormal changes in spleen and thymus indices, the colonic lesions, the unbalanced inflammatory factors levels like IL-10, IL-6, IL-1β, and TNF-α in serum, and the down-regulated intestinal permeability proteins such as Claudin-1, Occludin, and ZO-1. Experimental validation by WB confirmed that HRCR inhibited the expression of the key proteins, including MEKK1 RAS, ERK, IKB, and NF-kB, in the MAPK/NF-kB signalling in CAC mice.DiscussionHRCR not only suppresses the process of colonic inflammation and improves intestinal permeability but also relieves CAC by inhibiting the activated MAPK/NF-kB signalling cascade to alleviate CAC.